Ultra-fast high-resolution agarose electrophoresis of DNA and RNA using low-molarity conductive media. (October 2004) - Brody, Jonathan R.; Calhoun, Eric S.; Gallmeier, Eike; Creavalle, Talisa D.; Kern, Scott E.
Current DNA electrophoretic solutions employ high ionic concentrations and require long electrophoretic run times. Here we demonstrate that high and low molecular weight double-stranded DNA, single-stranded DNA (ssDNA), and RNA can be separated rapidly in agarose-based low-molarity conductive media. Separation of small DNA fragments was optimized by substituting 1-mM solutions of alkali metals or a nonbiological amine that distributed voltage with a minute current. These ultra-dilute solutions can separate DNA at least 15-fold faster. Low-molarity media at 5–10 mM adequately separated RNA and larger DNA fragments as well. These novel media reduce the Joule heating of the electrophoretic system and allow for easy-to-use, ultra-fast separation of DNA fragments.